Toward a Linguistically Responsive Teacher Identity: An Empirical Review of the Literature. Issue 4 (1st October 2016) - Martin, Adrian D.; Strom, Kathryn J.
ABSTRACT: Despite current demographic imperatives, little is known about how teachers understand, construct, and enact their professional identities in relation to teaching English learners (ELs). This article, an empirical review of the literature on teacher identity and ELs, examines how teacher identity has been investigated among educators working in English-dominant teaching contexts. Findings suggest that the literature has largely focused on three main facets of teacher identity: characteristics of teacher identity, factors contributing to teacher identity development, and contextual influences on teacher identity. Implications for promoting the development of a linguistically responsive teacher identity in education include the diversification of the teacher workforce, the incorporation of reflective practice among education practitioners, and fostering professional identity development for teachers of ELs.